Fetal mummification in a cow with twin gestation and retention of the fetuses in the vagina: a case report. - Araújo, Airton (2008)
This article describes the case of a 59-months old Brown Swiss cow raised in a semi-arid region of the Brazilian Northeast, with two mummified fetuses in the vagina. According to the herd records, the cow was at the seventh month of its second gestation when the fetuses were found in the vagina. The cow showed normal signs of estrus, such as mounting activity. The uterine horns showed no asymmetry and were contractile and turgid and there was no pus secretion from the vagina. Also, a pre-ovulatory follicle (18.5 mm) was present on the right ovary. The two mummified fetuses were confirmed to be males, measuring 12.1 cm and 11.5 cm, each. The mummification in this case is probably classified as “hematogenous”, once the fetuses were partially dry but not very hard covered with a bloody and viscous tissue. Release of fetuses from the uterus to the vagina allowed a normal involution of the uterus to its normal size, regression of the corpus luteum and return of hypothalamic-hypophyseal and gonadal activity, confirmed by the estrous behavior. After fetuses had been removed from the vagina, the cow received two doses of oxitetracycline at an interval of 48 hours to prevent uterine infections. The cow was observed in estrus 20 days later, inseminated and confirmed pregnant at 40 days of gestation by palpation per rectum.